Literatura de circulación masiva, de la producción a la recepción. El caso de los lectores de autoayuda - Papalini, Vanina Andrea (2019)
In this article we will analyze the “mass literature”, starting with a conception of literature that distances itself from those that make it correspond to a cultural norm, and which theoretical foundations are inspired both in Cultural Studies and the Aesthetics of Reception. For this, we will analyze a typical case of this “dominant” literature: self-help books. First, we carry out an analysis of the production of these books; later, we focus on their circulation and the composition of their readership, differentiating typical means of reception that let us construct some specific interpretive communities of the self-help genre.